Development of SNP genotyping arrays in two shellfish species - Lapegue, Sylvie; Harrang, Estelle; Heurtebise, Serge; Flahauw, Emilie; Donnadieu, C.; Gayral, P.; Ballenghien, M.; Genestout, L.; Barbotte, L.; Mahla, R.; Haffray, P.; Klopp, C. (Molecular Ecology Resources, 2014)
Use of SNPs has been favored due to their abundance in plant and animal genomes, accompanied by the falling cost and rising throughput capacity for detection and genotyping. Here, we present in vitro (obtained from targeted sequencing) and in silico discovery of SNPs, and the design of medium-throughput genotyping arrays for two oyster species, the Pacific oyster, Crassostrea gigas, and European flat oyster, Ostrea edulis. Two sets of 384 SNP markers were designed for two Illumina GoldenGate arrays and genotyped on more than 1000 samples for each species. In each case, oyster samples were obtained from wild and selected populations and from three-generation families segregating for traits of interest in aquaculture. The rate of successfully genotyped polymorphic SNPs was about 60% for each species. Effects of SNP origin and quality on genotyping success (Illumina functionality score) were analyzed and compared with other model and non-model species. Furthermore, a simulation was made based on a subset of the C. gigas SNP array with a minor allele frequency of 0.3 and typical crosses used in shellfish hatcheries. This simulation indicated that at least 150 markers were needed to perform an accurate parental assignment. Such panels might provide valuable tools to improve our understanding of the connectivity between wild (and selected) populations and could contribute to future selective breeding programs.